Impacting theatre audiences : methods for studying change - Omasta, Matt, 1980-; Snyder-Young, Dani, 1977- (Audience research., 2022)
"This edited collection explores methods for conducting critical empirical research examining the potential impacts of theatrical events on audience members. Dani Snyder-Young and Matt Omasta present an overview of the burgeoning subfield of audience studies in theatre and performance studies, followed by an introduction to the wide range of ways scholars can study the experiences of spectators. Consisting of chapter length case studies, the book addresses methodologies for examining spectatorship, including qualitative, quantitative, historical/historiographic, arts-based, participatory, and mixed methods approaches. This volume will be of great interest to theatre and performance studies scholars as well as industry professionals working in marketing, audience development and community engagement"--